Revisiting K.H. Hasyim Asy’ari’s Sufi Ethics in the Context of Contemporary Islamic Social Activism in Indonesia - Vateen Nayla Nurul Varyda; Rosidi Rosidi; Abdul Mun'im Cholil (Universitas Nurul Jadid, 2025)
In post-Reform Indonesia (1998–present), social challenges such as radicalism, moral disorientation, and identity fragmentation demand a religious approach integrating spirituality with social realities. This study revisits the ethical Sufism (tasawuf akhlaki) of K.H. Hasyim Asy'ari (1871–1947), founder of Nahdlatul Ulama and Pesantren Tebuireng, examining its contemporary relevance for Islamic social activism in Indonesia. Specifically, it analyzes how his Sufi ethics—rooted in sincerity (ikhlas), self-purification (tazkiyah al-nafs), moral conduct (adab), and spiritual struggle (mujahadah) are reappropriated by NU-affiliated organizations and pesantren-based movements addressing modern societal issues. Employing a qualitative historical-hermeneutic method, data were collected through close reading of Hasyim Asy'ari's original works (Adab al-'Alim wa al-Muta'allim, Risalah Ahl al-Sunnah wa al-Jama'ah), secondary sources, and academic journals documenting NU social initiatives (2000–2024). Findings reveal that his ethical Sufism functions as a moral framework cultivating social awareness and civic engagement, institutionalized through pesantren education and manifested in grassroots movements addressing religious pluralism, deradicalization, and community empowerment. This research contributes to recontextualizing Sufism in modern civic ethics by demonstrating how classical Islamic spirituality operates as a framework for contemporary social activism, bridging religious scholarship on tasawuf and sociological studies of Islamic movements. The study suggests further comparative research between pesantren-based moral education and global character formation models, plus empirical investigation into Sufi ethics' measurable impacts on community resilience.